An appraisal of Ireland's current legislative proposals for regulating domestic surrogacy arrangements. Issue 2 (3rd April 2019) - Tobin, Brian
ABSTRACT: This article critiques the complex hybrid model that has been proposed for regulating domestic surrogacy arrangements in Ireland, and the reasons why this model came about. It proposes an alternative model for regulating surrogacy, one that is in operation elsewhere and achieves a better balance between the rights of the surrogate, the intending parents and, most importantly, the surrogate-born child. The proposed establishment of the National Surrogacy Register, its interaction with the Register of Births and the issuing of 'surrogacy certificates' is also analysed, and a far less complex means of respecting the surrogate-born child's right to knowledge of its identity is proposed. The article concludes that Ireland's current legislative proposals for regulating surrogacy need to be substantially revised before ever being placed on the statute book. In their present form, they are so restrictive that, rather than facilitating domestic surrogacy arrangements, they are far more likely to discourage them.